Answer: Y = 3 × 2^x
Explanation:
Let assume that the equation of the exponential function represented by the table is
Y = 3(2)^x
When x = 0
Substitute x for 0. Then,
Y = 3 × 2^0
Anything raised to power of zero is equal to one.
Y = 3 × 1 = 3
When x = 1
Repeat the process
Y = 3(2)^1
Y = 3 × 2 = 6
When x = 2
Y = 3(2)^2
Y = 3 × 4 = 12
And finally, when x = 3
Y = 3(2)^x
Substitute x for 3
Y = 3 × 2^3
Y = 3 × 8
Y = 24.
We can therefore conclude that the equation of the exponential function represented by the table above is
Y = 3 × 2^x